2011
DOI: 10.1002/cbf.1800
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptotic death by curcumin in human tongue squamous cell carcinoma SCC-4 cells is mediated through endoplasmic reticulum stress and mitochondria-dependent pathways

Abstract: Curcumin from the rhizome of the Curcuma longa plant has been noted for its chemo-preventative and chemo-therapy activities, and it inhibits the growth of many types of human cancer cell lines. In this study, the mechanisms of cell death involved in curcumin-induced growth inhibition, including cell cycle arrest and induction of apoptosis in human tongue cancer SCC-4 cells, were investigated. Herein, we observed that curcumin inhibited cell growth of SCC-4 cells and induced cell death in a dose-dependent manne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 25 publications
5
27
0
Order By: Relevance
“…We found that curcumin induced caspasedependent apoptotic signaling pathways, accompanied by a decreased Bcl-2 expression and increased Bax and Cyt-c levels in NT2 cell lines. Similar to our findings, several studies have reported that curcumin decreased Bcl-2 levels in many types of cancer cells, such as squamous cell carcinoma (18), small cell lung cancer (19), myeloid leukemia (20) and adenocarcinoma cells (21). Our results are consistent with those from other reports of curcumin-mediated cytotoxic activity via the induction of apoptosis (22).…”
Section: Discussionsupporting
confidence: 93%
“…We found that curcumin induced caspasedependent apoptotic signaling pathways, accompanied by a decreased Bcl-2 expression and increased Bax and Cyt-c levels in NT2 cell lines. Similar to our findings, several studies have reported that curcumin decreased Bcl-2 levels in many types of cancer cells, such as squamous cell carcinoma (18), small cell lung cancer (19), myeloid leukemia (20) and adenocarcinoma cells (21). Our results are consistent with those from other reports of curcumin-mediated cytotoxic activity via the induction of apoptosis (22).…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, when compared with honey, turmeric may not have long-term adjunct effects as studies have shown it to be also beneficial in the treatment of various periodontal diseases. 40,[52][53][54] Literature studies also show that turmeric possesses selective antineoplastic activity on neoplastic cells, chemopreventive effects, and antimetastatic activities, [14][15][16][17][18][19][20][21][22][23] all of which can be beneficial in the prevention of recurrence and distant spread of the cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have confirmed that anti-cancer drugs including cisplatin [14] and Tetrocarcin-A [15] as well as anti-cancer neutral compounds such as curcumin [16][17][18] all activate ER stress to promote cell apoptosis. Here we studied whether ER stress play a role in ursolic acid's anti-bladder cancer ability.…”
Section: Introductionmentioning
confidence: 99%